CORRELATION ANALYSIS OF PARENTAL SUPPORT AND CONFIDENCE IN ADOLESCENTS WITH DEFENSE YOUTH - Andriani, Ayu; Lengkong, Felix (Psikoislamedia: Jurnal Psikologi, 2021)
Self-confidence is an important factor for adolescents who are deaf. Self-confidence is a form of feeling confident about the ability that an individual has to be able to achieve life goals. To get confidence, parental support is needed. Parental support causes teenagers to feel comfortable, feel loved and cared for. This study aims to determine the relationship between parental support and self-confidence of adolescents with hearing impairment at SLB-B Pangudi Luhur. The research method is quantitative. Data obtained through questionnaires that have been tested first. The number of samples in this study were 63 subjects, who were Pangudi Luhur SMPLB and SMALB students aged 13-18 years. Based on the results of data analysis, it is known that the correlation coefficient between parental support and self-confidence is 0.609 with a significance level of 0.000. This means that there is a relationship between parental support and the confidence of adolescents with hearing impairment at the SLB-B Pangudi Luhur. This means that the higher parental support, the higher the confidence of adolescents with hearing impairment in the SLB-B Pangudi Luhur.